Bacterial coinfections on foliar blight and bulb rot in onion (Allium cepa L.) - Jiménez-Acero, Juan Carlos (2023)
Introduction. The onion bulb (Allium cepa L.) is a cultivated vegetable characterized by its fleshy scales susceptible to phytopathogen attacks causing economic losses. The symptoms of foliar wilting, blighting, and rot of bulb can be caused by different genera and bacterial species that can co-infect the host, making it difficult to identify the causal agent. Objective. To evaluate the effect of bacterial co-infections on foliar wilt and bulb rot in onion. Materials and methods. The bacteria were isolated from onion plants with symptoms of leaf blight and bulb rot, from crops located in Choachí Cundinamarca, Colombia, collected in June 2018. Bacterial isolates were purified, identified, and inoculated individually and in a mixture on healthy onion leaves and bulbs. Six treatments per organ were evaluated: three with individual infections and three with co-infection. The lesion progress was measured in both organs for twelve days after inoculation. Results. Two bacterial species identified as Pantoea ananatis and Rahnella aquatilis were obtained from the foliar and bulb symptoms. In individual infections, the P. ananatis strain presented the highest virulence causing 34.29 % bulb damage, and 100 % leaf damage, while the R. aquatilis generated the lowest percentage of rotting in the bulb (8.87 %) and it did not produce wilt. In co-infections, the combination of P. ananatis and R. aquatilis produced the lowest percentages of bulb (15 %) and leaf (10 %) damage, associated with a decrease in the symptom’s expression. Conclusion. R. aquatilis acted as an antagonistic organism of P. ananatis and causes a delay in the development of foliar wilt and bulb rot symptoms in onion.